PENGARUH STATUS SOSIAL EKONOMI ORANG TUA, MOTIVASI BELAJAR, DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR PADA SISWA SMK BARUNAWATI SURABAYA - Rizkiana, Atya (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The purpose of this study was to determine the effect of socioeconomic status, learning motivation, and learning disipline on student achievement at SMK Barunawati Surabaya. This study quantitative methods as a research methodology descriptive design. Population in this study are tenth grades students in SMK Barunawati Surabaya who are 103 students. Sampel was 82 students, selected by using Proporsional Random Sampling. Data analysed using multiple regression analysis. The result showed that socioeconomic status, learning motivation and learning discipline has partially significant impact on student achievement. Socioeconomic status, learning motivation and learning discipline have a significant impact on student achievement